Budaya Masyarakat Madura Sebagai Sishankamrata (Sistem Pertahanan Rakyat Semesta) - Adelia Prameisty; Kuntum Chairum Ummah (Journal of Social, Culture, and Language, 2024)
This research aims to analyze the character of Madurese society as a model of national defense by applying systems theory. The character of the Madurese people, which includes values such as courage, resilience and the spirit of never giving up, is studied as a subsystem within the framework of a larger system, namely the Indonesian nation. These characteristics are seen in the context of interaction with the national system and its impact on national defense. System theory is used to understand the relationship between the character of the Madurese people and national defense, as well as to explain their role in maintaining the integrity of the country. The results of this study provide insight into how the character of the Madurese people can is considered an important asset in national defense and has practical implications in efforts to strengthen national resilience. This study also details the importance of balance, adaptation, support and integration in utilizing the character of the Madurese people as a valuable resource in national defense. This research provides the basis for more effective planning and policy, utilizing Madurese personality for defense purposes. Keywords : Culture, Defense, System